Popping the K-Pop bubble A study on the world of K-pop fandom as a subculture - Pacis, Jessamine Joyce Caunte (2012)
"This study is about the Korean pop (K-pop) music fan culture in the Philippines. It describes how the culture developed, and how the fans interact with one another in the fan community. It elaborates on the nuances of the K-pop fan community and aims to answer the primary research question, How is power exercised and negotiated in the interactive and productive practices of Filipino K-pop fans? Through the methods of document analysis and autoethnography, the interactions and relations among K-pop fans were analyzed using Subcultural Theories by Henry Jenkins, John Fiske and Sarah Thornton, and Jenkin's work in participative fan culture. The researcher was able to come up with three primary conclusions: 1) that the K-pop fan community is a subculture rich with politics and relations of power; 2) that media play a significant role in the preservation of this subculture; and that 3) the Korean government is actively involved in the development of K-pop fandom. The study is expected to foster a deeper understanding of local fan culture and how it relates to the discourse of globalization. Its major implications are on how media texts can be tools for the creation of new communities and the development of subcultures."